Spin Transfer Torque (STT) Based Devices, Circuits, and Memory. - Kaushik, Brajesh Kumar (Artech House, 2016)
This first-of-its-kind resource is completely dedicated to spin transfer torque (STT) based devices, circuits, and memory. A wide range of topics including, STT MRAMs, MTJ based logic circuits, simulation and modeling strategies, fabrication of MTJ CMOS circuits, non-volatile computing with STT MRAMs, all spin logic, and spin information processing are explored. State-of-the-art modeling and simulation strategies of spin transfer torque based devices and circuits in a lucid manner are covered. Professional engineers find practical guidance in the development of micro-magnetic models of spin-torque based devices in object-oriented micro-magnetic framework (OOMMF) and compact modeling of STT based magnetic tunnel junctions in Verilog-A. The performance parameters and design aspects of STT MRAMs and MTJ based hybrid spintronic CMOS circuits are covered and case studies are presented demonstrating STT-MRAM design and simulation with a detailed analysis of results. The fundamental physics of STT based devices are presented with an emphasis on new advancements from recent years. Advanced topics are also explored including, micromagnetic simulations, multi-level STT MRAMs, giant spin Hall Effect (GSHE) based MRAMs, non-volatile computing, all spin logic and all spin information processing.